The acquisition of trisomy 8 associated with Behçet's-like disease in myelodysplastic syndrome. (2020) - Oka, Satoko; Ono, Kazuo; Nohgawa, Masaharu
Abstract: A relationship has been reported between myelodysplastic syndrome (MDS) and autoimmune disease. Behçet's disease is a multisystem inflammatory disorder with mucocutaneous, articular, gastrointestinal, neurological, and vascular manifestations. The co-occurrence of MDS with trisomy 8 and Behçet's-like disease was recently demonstrated. We herein describe a case that shows the relationship between the acquisition of trisomy 8 and occurrence of Behçet's-like disease. Immune dysregulation and altered T-cell hemostasis play an important role in the pathogenesis of Behçet's-like disease and MDS with trisomy 8.